The assessment of foreign market entry strategies: a case on Trurich Resources Sdn Bhd (TRSB) venturing into Indonesian market / Muhammad Zaidi Zainal Abidin - Zainal Abidin, Muhammad Zaidi (Faculty of Business and Management, 2013)
Globalization has widening the scope of world economy, increases the level of cooperation, and revolutionized the traditional business practices into international business expansion. Nowadays, foreign direct investment (FDI) has become popular among the big corporations as a medium to enter into foreign market. To ensure the successful in foreign market, firms must first evaluate the respective market. The main objective of this study is to identify the assessment, strategies and barriers encountered by Trurich Resources Sdn. Bhd. when they venturing into foreign market. The assessments studied are based on Dunning Eclectic Theory (OLI), Internalization theory, Foreign Market Entry Strategies and Porter’s Theory of Nation Competitive Advantages. Other international strategies such corporate strategy, business strategy, Porter’s Generic Strategies and integrative strategies also were included into the study to further identify the company’s strategies and barriers encountered to achieve such objectives. The data was collected primarily through a series of interview session with Trurich Resources’ top management; Mhamod Bin Mokhtar (CEO), Ramli Bin Mohd Tahar (General Manager) and Mohamad Azhar Bin Abd Rahman (Estate Manager). Some of the data were obtained from the researcher observations, industry review, statistical records and internet. The data collected shows that the company owned the three advantages (OLI) as per described in Dunning Eclectic theory. The Porter’s Nation Competitive Advantages also do reflect with the company’s succession in international expansion. While the host country governance, rules and regulations, bureaucracy and the world market were identified as the barriers for the company’s strategy.